The value of stability in photovoltaics - Peters, Ian Marius; Brabec, Christoph; Sinha, Parikhit; Hauch, Jens (Joule, 2021)
Warranties for photovoltaic modules last 25 years. The same duration is frequently used when predicting economic performance. Yet, many modules still produce more than 80% of their original power after 25 years, and there is no economic reason to retire them. Here, we adopt a different mindset: photovoltaic installations are operated indefinitely with maintenance at regular intervals. We reflect this view in a steady-state economic model. We find that in this view, maintenance gains in value -33% compared with a 30-year lifetime-and time constraints for maintenance are lifted. We also find that stability becomes even more important. Reducing annual degradation from 0.5% to 0.2% entails a 12 ct/Watt cost entitlement, increases the economically useful lifetime by a factor of 1.69, defers end of life by decades, and reduces resources and infrastructure needed for recycling by 40%. We foresee that modules installed today should ideally be operated for 50 years.
CRIS-Team WoS Importer:2022-01-07